Time trends in mental health indicators in Germany's adult population before and during the COVID-19 pandemic - Mauz, Elvira; Walther, Lena; Junker, Stephan; Kersjes, Christina; Damerow, Stefan; Eicher, Sophie; Hölling, Heike; Müters, Stephan; Peitz, Diana; Schnitzer, Susanne; Thom, Julia (Frontiers in Public Health, 2023)
Background Times of crisis such as the COVID-19 pandemic are expected to compromise mental health. Despite a large number of studies, evidence on the development of mental health in general populations during the pandemic is inconclusive. One reason may be that representative data spanning the whole pandemic and allowing for comparisons to pre-pandemic data are scarce. Methods We analyzed representative data from telephone surveys of Germany’s adults. Three mental health indicators were observed in approximately 1,000 and later up to 3,000 randomly sampled participants monthly until June 2022: symptoms of depression (observed since April 2019, PHQ-2), symptoms of anxiety (GAD-2) and self-rated mental health (both observed since March 2021). We produced time series graphs including estimated three-month moving means and proportions of positive screens (PHQ/GAD-2 score ≥ 3) and reports of very good/excellent mental health, as well as smoothing curves. We also compared time periods between years. Analyses were stratified by sex, age, and level of education. Results While mean depressive symptom scores declined from the first wave of the pandemic to summer 2020, they increased from October 2020 and remained consistently elevated throughout 2021 with another increase between 2021 and 2022. Correspondingly, the proportion of positive screens first decreased from 11.1 % in spring/summer 2019 to 9.3 % in the same period in 2020 and then rose to 13.1 % in 2021 and to 16.9 % in 2022. While depressive symptoms increased in all subgroups at different times, developments among women (earlier increase), the youngest (major increase in 2021) and eldest adults, as well as the high level of education group (both latter groups: early, continuous increases) stand out. However, the social gradient in symptom levels between education groups remained unchanged. Symptoms of anxiety also increased while self-rated mental health decreased between 2021 and 2022. Conclusion Elevated symptom levels and reduced self-rated mental health at the end of our observation period in June 2022 call for further continuous mental health surveillance. Mental healthcare needs of the population should be monitored closely. Findings should serve to inform policymakers and clinicians of ongoing dynamics to guide health promotion, prevention, and care.